Propensity for adventurousness in the motivational structure of junior athletes - Popovych, I.; Kolly-Shamne, A.; Piletska, L.; Soroka, O.; Hoian, I.; Yaremchuk, V.; Huzar, V. (Journal of Physical Education and Sport, 2024)
This study aims to establish statistical correlations between the propensity for adventurousness and components of junior athletes' motivational structures.